AVALIAÇÃO DA POLÍTICA DE SAÚDE INDÍGENA FEDERAL NO ESTADO DO MARANHÃO FACE À PANDEMIA DO COVID-19 (2020-2022): Uma análise do caso da comunidade indígena Canela Memortumré - SILVA FILHO, Jofran Conceição da (2024)
This dissertation addresses the effectiveness of public health policies aimed at indigenous peoples in Brazil during the Covid-19 pandemic, with a focus on the Canela Memortumré indigenous community in the state of Maranhão. Throughout the country's history, indigenous peoples have faced various forms of land expropriation and loss of cultural identity, resulting in serious health problems due to lack of access to basic resources and environmental degradation. Using a methodological approach that combines political analysis and historical materialism, this study investigates the motivations behind public policies, the actors involved, and the perspective of indigenous peoples themselves. Through bibliographic, documentary research, and semi-structured interviews, both the historical aspects of indigenous health policies and the federal government's response during the pandemic were analyzed. The results revealed shortcomings in the administration of indigenous health policies, with a lack of minimum health access, lack of clean water, and shortages of medicines in the villages. The analysis also highlighted indigenous resistance and the importance of considering the voices of affected communities when assessing public policies. This dissertation contributes to understanding indigenous health policies in Brazil and emphasizes the need for a more inclusive and effective approach to ensure the well-being of these vulnerable communities during crises such as the Covid-19 pandemic.